Relationship between advanced lung cancer inflammation index and all-cause and cause-specific mortality among chronic inflammatory airway diseases patients: a population-based study - Zhuanbo Luo; Peixu Chen; Shiyu Chen; Xue Kong; Hongying Ma; Chao Cao (Frontiers in Immunology)
BackgroundChronic inflammatory airway diseases (CIAD), such as asthma, chronic bronchitis, and chronic obstructive pulmonary disease, pose a significant threat to public health, with its prognosis closely tied to the body’s inflammation level and nutritional status. As a composite indicator, the advanced lung cancer inflammation index (ALI) integrates inflammation and nutritional status. Despite its potential utility, the link between ALI and the prognosis of patients with CIAD remains unexplored. This study aimed to investigate this relationship.MethodsWe gathered data from the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018. The National Death Index was used to calculate mortality until December 31, 2019. Kaplan-Meier analysis was employed to investigate the relationships between ALI and all-cause and cause-specific mortality in patients with CIAD. Furthermore, weighted univariable and multivariable Cox proportional hazards models were employed to further examine their relationship. Multiple factors that could impact the results were adjusted in the analysis. We also utilized a restricted cubic spline analysis to estimate the non-linear relationships between ALI and all-cause and cause-specific mortality rates in patients with CIAD. Finally, subgroup and sensitivity analyses were conducted to ensure the reliability of the findings.ResultsThe study involved 2,884 CIAD patients. An elevated ALI was significantly related to a decreased risk of all-cause mortality, as well as mortality from cardiovascular and respiratory diseases among CIAD patients. Results from RCS analysis revealed a reverse J-shaped non-linear association between ALI and all-cause mortality in CIAD patients, with an inflection point at 99 (p for nonlinearity <0.0001). The inflection point in the J-shaped relationship represents the ALI value with the lowest risk of mortality. For ALI values below 99, a 10-unit rise in ALI was linked to a 14% reduction in the risk of all-cause mortality (HR: 0.86, 95% CI:0.81-0.92, Ptrend=0.01). Conversely, if ALI exceeded 99, a 10-unit increase in ALI resulted in a 3% rise in the risk of all-cause mortality (HR: 1.03, 95% CI:1.01-1.06, Ptrend=0.02). A similar J-shaped association was observed in mortality due to cardiovascular and respiratory diseases, with inflection points at 94 and 96, respectively. These findings were consistent across sociodemographic and prior disease-related subgroups, and remained stable in sensitivity analyses.ConclusionThis study revealed a novel association between elevated ALI level and reduced all-cause and cause-specific mortality risk in patients with CIAD. Furthermore, the relationship between ALI and mortality rates from all cause, as well as cardiovascular and respiratory diseases, exhibited an non-linear, J-shaped curve. These findings underscore the importance of maintaining optimal ALI levels within a specific range to promote long-term survival in CIAD patients. The dynamic variation in ALI over time also can help clinicians establish personalized ALI standards to maximize the long-term outcomes for CIAD patients.